NEONATOLOGIST'S TACTICS IN CASES OF NEWBORN CONGENITAL MALFORMATION - Y. I. Kucherov (Педиатрическая фармакология)
Mortality of congenital malformation is the 2nd most widespread cause of death among newborns. Mortality reduction is the priority aim of practical healthcare in our country. Early detection and rational therapy whereupon a child is born to a large extent determine a favorable outcome of surgical treatment and prognosis in whole. The article gives a description of the most frequent congenital malformations and an algorithm of managing newborns with this pathology on the maternity hospital stage.